Transcatheter Aortic Valve Implantation Current Indications and Future Directions - Winkel, Mirjam Gauri; Stortecky, Stefan; Wenaweser, Peter (Frontiers in Cardiovascular Medicine, 2019)
Degenerative heart valve disease is associated with significant morbidity and mortality and healthcare expenditures. Transcatheter heart valve repair and replacement has introduced a fundamental change in the therapeutic management and transcatheter aortic valve replacement (TAVR) has gained substantial popularity. Favorable results from randomized trials and large real world registries lead to TAVR being considered a standard procedure with high rates of procedural success and low rates of peri-procedural complications. This article aims to review the past evolution, summarize the available evidence, discuss current indications and limitations and venture a glimpse into the future of percutaneous interventions for aortic valve disease.